Differential Impacts on Human Physiological Responses on Heatwave and Non-Heatwave Days: A Comparative Study Using Wearable Devices in Beijing - Tong Sheng; Qi Liu; Yumeng Kou; Guole Shang; Miaomiao Xie (Atmosphere)
As global warming intensifies heatwave events, their impact on human health is becoming increasingly significant. To further understand the dynamic response of humans to heatwaves, this study selected samples from different age groups under various thermal conditions in Beijing, China. Physiological parameters, including blood pressure, blood glucose, heart rate, blood oxygen, and body temperature, were monitored during both heatwave and non-heatwave periods using wearable devices. The results show that during heatwaves, the average blood pressure increased by about 10%, blood glucose levels rose by about 4%, heart rates increased by about 12%, and blood oxygen levels decreased by an average of about 7%. These effects were particularly pronounced in people aged 50 and above, with heart rate and blood oxygen saturation showing significant age-related differences. The study indicates that heat waves have a more substantial impact on the elderly population, with age being a key factor in determining physiological responses to extreme heat. Therefore, it is necessary to develop age-specific health management strategies to address vulnerability under high-temperature conditions.